God's Gifts: Destiny, Poverty, and Temporality in the Mines of Sierra Leone. Issue 1 (April 2019) - D'Angelo, Lorenzo
In Sierra Leone, many artisanal miners share the view that every human act and every event is the realisation of an inscrutable divine plan. Even though notions of fate and destiny are part of the vocabulary of Krio, the country's lingua franca, miners prefer to use expressions that evoke God and stress His immanent presence and influence in their everyday lives. In order to understand the religious vocabulary of contingency and the cosmology underlying the ways in which miners interpret, reproduce, and imaginatively prepare the conditions to change their lives, this article focuses on the ritual practices connected to artisanal diamond mining. It considers these rituals as attempts to resolve the ever-present temporal and moral tensions between actual conditions of suffering and poverty, and the realisation of the well-being that miners associate with their desired futures.